The Effect of Perceived Social Media Marketing Activities on Brand Loyalty through Brand Consciousness and Value Consciousness on Vivo Smartphone - Chrein Yonathan Yoel .; Lena Ellitan; Robertus Sigit Haribowo Lukito . (Journal of Entrepreneurship and Business, 2021)
This research was conducted to determine the influence of Social Media Marketing Activities on Brand Loyalty through Brand Consciousness and Value Consciousness in Vivo smartphone. This research is casual research. The sampling technique uses non probability sampling by purposive sampling by purposive sampling. Respondents in this study were Vivo smartphone users and followed one of the Vivo smartphone social media. While the sample is 100 respondents. Data in this study were collected by distributing questionnaires using Google Form (online). The data analysis technique used is Structural Equation Modeling (SEM) using the SmartPLS 3 program. The result in this research indicate that: Perceived Social Media Marketing Activities has a positive and significant effect on Brand Loyalty, Brand Consciousness and Value Consciousness. Brand Consciousness has a positive and significant effect on Brand Loyalty. Value Consciousness has no effect Brand Loyalty. Perceived Social Media Marketing Activities through Brand Consciousness and Value Consciousness has no effect on Brand Loyalty in Vivo smartphone users